PENGARUH UKURAN DEWAN KOMISARIS DAN PROFITABILITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Akbar, Jordy Pamungkas; Taufiq, Eindye; Murtatik, Sri (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
This study was conducted to examine the effect of variable Board Of Commissioner and Profitability On Corporate Social Responsibility. The population in this study amounted to 39 mining companies go public registered on the Indonesia Stock Exchange during 2009 to 2013. Samples were obtained in this study of 10 companies selected with a three years observation period by purposive sampling method. The data obtained from the company’s annual report published. The analysis technique used in this study is a multiple linear regression and hypothesis testing using the classical assumption test , t - and F - statistics with a significance level of 5%. The results showed that all the independent variables that Board Of Commissioner and Profitability proved to be a significant on Corporate Social Responsibility.